Comparison of Three Imaging Methods for the Evaluation of Osteoarthritis Induced by Cranial Cruciate Ligament Transection in Rabbits - Brombini, Giovanna Cristina; Rahal, Sheila Canevese; Santos, Ivan Felismino Charas dos; Mamprim, Maria Jaqueline; Tsunemi, Miriam; da Silva, Jeana Pereira; Doiche, Danuta Pulz; Joaquim, Jean Guilherme Fernandes (Acta Scientiae Veterinariae, 2021)
Background:Osteoarthritis is a degenerative joint disease that affects specially cartilage, meniscus, and tendons. Ligaments, muscles, subchondral bone and synovium. This pathology is a common condition limiting the quality of life of patients. Imaging modalities have also been used for evaluation the progression of the osteoarthritis, or degenerative processes induced by acute injury. In order to use more accessible imaging modalities for experimentation, this study aimed to compare radiographic, computed tomography, and ultrasound findings in the evaluation of osteoarthritis induced by the cranial cruciate ligament transection model in rabbits. Materials, Methods & Results:Twenty-four male Norfolk rabbits aged approximately 5 months old were used. All rabbits were submitted to cranial cruciate ligament transection of the left stifle and evaluated 45 days after the surgery. The radiographic findings were subchondral bone sclerosis (33.33%); joint space narrowing (66%); presence of osteophytes at medial femoral condyle (4.16%), lateral femoral condyle (4.16%), medial fabela (20.83%), lateral fabela (8.33%) and sesamoid of the popliteal muscle (4.16%). No osteophytes were seen at medial and lateral tibial condyles. The tomographic computed findings were joint space narrowing (62.5%); presence of osteophytes at medial femoral condyle (75%), lateral femoral condyle (54.16%), medial fabela (66.66%), lateral fabela (37.5%), medial tibial condyle (75%), lateral tibial condyle (20.83%) and sesamoid of the popliteal muscle (37.5%). The ultrasound findings were synovial hypertrophy (95.83%); effusion in the suprapatellar recess (75%), distal tibial recess (16.66%) and cranial joint space (75%); changes (hyperechogenic foci and heterogeneity) of the lateral meniscus (50%) and medial meniscus (25%); increased thickness of the medial condyle (54.16%) and lateral condyle (45.83%); irregularity of the medial condyle (66.66%) and lateral condyle (58.33%); alterations of the patellar tendon (12.5%) and extensor ligament (effusion and increased echogenicity) (20.83%). Discussion: Osteoarthritis is a degenerative joint disease and is common condition which limiting the quality of life of patients. Many studies performed in rabbits have evaluated the development of osteoarthritis through post-mortem macroscopic or microscopic assessments. Imaging modalities have also been used for evaluation the progression of the osteoarthritis, or degenerative processes induced by acute injury. High quality radiographs are accurate in identifying structural changes resulted from osteoarthritis, but computed tomography allows earlier identification in relation to conventional radiography. The three imaging modalities were helpful to identify the osteoarthritis, but the findings were different and compatible with each analysis method. The computed tomographic detected a higher number of osteophytes than plain radiographs. Also, osteophytes did not visualized by radiographic examination, such as medial tibial condyle and lateral tibial condyle, were identified by computed tomography. In turn, the ultrasound examination <span style="font-size: 12pt; line-height: 200%; font-family: ’Times New Roman’, serif; background-image: initial; background-position: initial; background-size: initial; background-repeat: initial; background-attachment: initial; background-origin: initial; background-clip: initial;" lang="EN-US">enabled identification of lesions did not seen on radiographic and computed tomography examinations. Synovial hypertrophy and joint effusion had the highest percentage. In human patients, ultrasound examination has been used to assess hypertrophy and inflammation of the synovium due to osteoarthritis. In conclusion, computerized tomography images provided more information than plain X-ray images and can be complemented by ultrasound examination to identify osteoarthritis induced by cranial cruciate ligament <span style="color: #4d5156; background-image: initial; background-position: initial; background-size: initial; background-repeat: initial; background-attachment: initial; background-origin: initial; background-clip: initial;">transection in rabbits. <span style="font-size: 12pt; line-height: 115%; background-image: initial; background-position: initial; background-size: initial; background-repeat: initial; background-attachment: initial; background-origin: initial; background-clip: initial;" lang="EN-US">Comparison of Three Imaging Methods for the Evaluation of Osteoarthritis Induced by Cranial Cruciate Ligament <span style="font-size: 12pt; line-height: 115%; font-family: ’Times New Roman’, serif; background-image: initial; background-position: initial; background-size: initial; background-repeat: initial; background-attachment: initial; background-origin: initial; background-clip: initial;" lang="EN-US">Transection in Rabbits